PENGARUH VISKOSITAS SOL DAN PRESOLIDIFIKASI PADA PROSES GELASI EKSTERNAL DALAM PEMBUATAN GEL AMMONIUM DIURANAT MENGGUNAKAN SURROGATE CERIUM - Sukarsono; Rachmawati, Meniek (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The external gelation process is used in the preparation of ammonium diuranat gel with processed into UO2 coated particles. UO2 coated particles are the core of high temperature reactor (HTR) fuels. This paper reported the research of gel preparation though external gelation process using a surrogate of zirconium stabilized cerium. The purpose of this study was to determine the effect of sol viscosity and presolidification related to gel roundness which was produced in the operation of the gelation unit in the laboratory of High Temperature Nuclear Reactor Fuel. The parameters studied were sol viscosity by varying the addition of additive and gelation process with presolidification (with NH3 gas stream) and without presolidification (without NH3 gas flow). The Ce-Zr gel can be prepared through a similar process of ADU gel preparation. A mixture of cerium and zirconium nitrate solution with Ce content of 12 mole %, was added by urea as a pH regulator and added by additive materials of tetra hydrofurfuryl alcohol (THFA) and poly vinyl alcohol (PVA). The solution was ready to be used in the gelation process. Sol solution was fed into the gelation column by pressing using compressed air. The sol solution entered the gelation column through the dripping node nozzle was vibrated with frequency of 90-110 Hz and certain amplitude. The droplets was passed on a column containing NH3 gas so that occurred presolidification on the surface of the droplets. The drops fall to the solution medium containing NH4OH in the gelation column. The compaction occurred due to the polymerization of cerium nitrate and zirconium nitrate at a pH of about 10. The gel was accommodated in a container located under the gelation column and allowed to be at least 2 hours to complete the solidification. The gel was washed successively with aqueous NH4OH, water and isopropyl alcohol and continued by drying. Operation of the gelation column to produce a round and uniform gel required adjustment the frequency, amplitude and flow rate of the sol solution. Operation of gelation columns at a frequency of 100 Hz using a sol with a viscosity of 97 cP and a flow rate of 25.8 mL/min produced a gel with smooth, uniformity and a relatively good sphere. For sol with a viscosity of 56 cP had relatively good flow rate was 28.8 mL/min and at a low viscosity of 46 cP, a flow rate of 30 ml/min is obtained. Operating the gelation device at frequencies of 110 Hz, 100 Hz and 90 Hz, produced a smooth, uniform and round gel at a sol flow rate of 27.9 mL/men, 25.8 mL/min and 21.2 mL/min. The gelation process with NH3 gas stream as a presolidative medium produced a more rounded and uniform gel than with no NH3 gas stream that resulted the non-round gel. From this studied it could be concluded that the viscosity of the sol and the vibration frequency of the dropout nozzle affects the flow rate of the sol but did not affect the gel roundness. The larger viscosity of solution, the smaller the flow rate of the sol to get a separate, uniform and round gel. The greater vibrational frequency also increases the flow rate to get a good gel. The gelation process without presolidification resulted a non-round gel.